Seroepidemiology of Toxoplasma gondii, Neospora caninum, and Leishmania spp. infections and risk factors for cats from Brazil - Dourado Coelho, Willian Marinho [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Apolinario, Juliana de Carvalho [UNESP]; Dourado Coelho, Natalia Marinho [UNESP]; Felix de Lima, Valeria Marcal [UNESP]; Venturoli Perri, Silvia Helena [UNESP]; Saraiva Bresciani, Katia Denise [UNESP] (Springer, 2011)
The seroprevalence of infection by Toxoplasma gondii, Neospora caninum, and Leishmania spp. was detected through an indirect immunofluorescence in 70 cats from the Andradina Municipality, São Paulo State, Brazil. Anti-T. gondii antibodies (titer >64) were detected in 15.7% (11/70) of animals, whereas positivity for N. caninum (titer 16) was not observed in any animal. of the cats from urban and rural areas, 10.4% (5/48) and 27.2% (6/22) were positive for T. gondii, respectively. Breed, age, food, and contact with animals of other species were significant for considering the positivity for T. gondii (P <= 0.0001). Cats having access to streets (17.1%, 11/64), cats cohabiting with rats (19.6%, 10/51), and cats feeding on homemade food and raw milk (27.2%, 6/22) were positive for T. gondii. In addition, 4.2% (3/70) of the cats were positive for Leishmania spp. by ELISA technique and negative by IFAT without coinfection with T. gondii and Leishmania spp. There was no serological positivity against feline immunodeficiency virus or feline leukemia virus. In conclusion, T. gondii infection in part of the feline population from Andradina is not linked to immunosuppressions or coinfections but probably to postnatal infection in association with the type of diet and presence of rats.